Error analysis in social media caption: a study on Instagram - Wardoyo, Aprilia Thianli; Rais, Burhanudin; Yunia, Amilda Ellay (Journal of English Language and Pedagogy (JELPA), 2023)
Many people idolize using English captions on their social media. However, some of them create errors in writing the caption. This error can cause misinterpretation by the reader. On this basis, the researchers aim to analyse the writing mistake in social media captions. The selected social media in this research was Instagram. The researchers conducted research over several months. This research was conducted by following descriptive qualitative research, in which the respondents were young adults of Instagram Users from Sintang. This research was conducted by analysing the mechanics and language use components. By the end of this research, the researcher found that the biggest mistake was the misformation type, which consisted of 35%, and the lowest was addition error. However, this result does not reveal the Sintang people's English capability. The researchers only analyze frequent errors made in the Instagram caption.